Optimizing Village Assets as a Source of Local Economic Empowerment: A Mentoring Program in Bulangan Barat, Pegantenan, Pamekasan - Zainatul Mufarrikoh; Fitriyatul Qomariyah; Moh. Syafik; Fera Rahmawati; Rofiqi Rofiqi (Warta LPM, 2026)
Bulangan Barat Village has durian assets distributed across nearly the entire village, making it as a potential leading commodity for community economic empowerment. The results of the 2024 PKM asset mapping indicate that while most residents own durian trees, productivity remains low due to limitations in maintenance techniques, fertilization, pest control, and harvesting practices. This program aims to enhance community capacity through an Asset-Based Community Development (ABCD) approach that optimizes local assets. The activities were conducted through two technical assistance sessions involving 15 participants, including training and socialization on the development of local durian commodities, as well as field assistance in Dusun Utara and Dusun Barat. These activities were followed by monitoring and evaluation. The results show that 2 out of 15 participants (13.3%) began applying more appropriate fertilization techniques, including installing fertilizer pipes to reduce flower drop in durian trees. In addition, one participant started diversifying crops by cultivating melon as an alternative commodity to durian. The community’s managerial capacity is demonstrated by initiatives to coordinate the certification process for local durian varieties and by the use of a WhatsApp group consisting of 16 members (1 expert, 3 facilitators, and 12 durian farmers) as a platform for information exchange and coordination in managing the durian commodity. As a follow-up, the program requires strengthened sustainability through periodic and structured ongoing assistance to increase the even adoption of technology. Future community service activities focus on continued support for the development and certification of local durian varieties to improve productivity, crop quality, and sustainably restore the prominence of local durian in Pegantenan District.